Energy-saving system of secondary balance for the hybrid power of the pumping unit - Chun-shuang Li; Lin Chen; Xin Wang; Kui Sun; Xin-hui Liu (The Journal of Engineering, 2018)
The pumping unit is the main equipment for oil production in the oilfield. However, its serious energy consumption has greatly increased the cost of oil extraction. The reason of this phenomenon is the undesirable primary and secondary balance cannot make the motor run steadily in the high efficiency load rate interval, leading to low efficiency and great loss of the motor. In this paper, the secondary balance system for hydraulic hybrid power of pumping unit is developed, which can store the potential energy of the lower stroke in the accumulator and release it in the up stroke. It can effectively fill and reduce the wave valley and peak of the load rate curve, so that the motor can run in the high efficiency for a long time. The controller of the secondary balance system has a self-learning method based on the multiple populations' genetic algorithms. It can reflect the real load by detecting the motor operating parameters, improving the response speed. At last, use AMEsim to simulate the hydraulic system, and compare the load fluctuation and motor energy consumption before and after setting energy-saving system. It is proved that the energy saving effect of the system is extremely remarkable.